نسبة مساهمة بعض المتغيرات البدنية الخاصة والبايوميكانيكية لأداء التصويب من الثبات في كرة السلة - حەمەصاڵح, بەڵێن قادر; خان, حسن عبدالكريم رستم (Sulaimani Journal for Humanities, 2022)
The importance of the research was manifested in revealing the percentage of the contribution of some special physical and biomechanical variables to the performance of shooting stability in basketball in order to know and reach the reasons for the weakness of players in the performance of this skill. The goals of the research were: to identify the relationship between some of the special physical and biomechanical variables, as well as the percentage of their contribution to the performance of shooting from stability in basketball. The most important conclusions were: The biomechanical variables are positively correlated with the performance of the shooting skill from stability in basketball. It was recommended: The need to focus on applying the principles and basics of biomechanical variables during training units in a consistent manner with the requirements of motor performance for the skill of shooting from stability in basketball.